2019
DOI: 10.1097/coh.0000000000000572
|View full text |Cite
|
Sign up to set email alerts
|

Prisons

Abstract: Purpose of review-People with HIV and HCV are concentrated within criminal justice settings globally, primarily related to criminalization of drug use. This review examines updated prevention and treatment strategies for HIV and HCV within prison with a focus on people who inject drugs and the challenges associated with the provision of these services within prisons and other closed settings and transition to the community. Recent findings-The prevalence of HIV and HCV are several-fold higher in the criminal j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…In many countries with condom program in prisons, coverage of the program is either low or unknown [ 19 ]. In other words, it is unclear what proportion of prisoners has access to condoms.…”
Section: Discussionmentioning
confidence: 99%
“…In many countries with condom program in prisons, coverage of the program is either low or unknown [ 19 ]. In other words, it is unclear what proportion of prisoners has access to condoms.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies 4,8 in the review suggested 'decriminalization' policies as a step towards reducing the overall HCV burden in prisons.…”
Section: A System Wide Approachmentioning
confidence: 99%
“…Two studies 4,8 in the review suggested ‘decriminalization’ policies as a step towards reducing the overall HCV burden in prisons. ‘Decriminalization’ describes the removal of criminal sanctions against an act or behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…MAT in prison has also been associated with reduced rates of infectious diseases. Adequate MAT has been associated with reduced risk of HCV infection (Dolan et al, 2005;UNODC/UNAIDS, 2006;Dolan et al, 2016;Azbel et al, 2018;Kamarulzaman et al, 2019), whereas inadequate MAT -periods of less than five months in one study, for example -was found to be significantly associated with increased risk of HCV seroconversion (P = 0.01) . People living in prisons receiving MAT with a daily dose of more than 60 mg during their whole prison sentence were found to be the least likely to inject heroin, share needles, and engage in HIV risk-taking behaviour while in prison (Dolan et al, 2003).…”
mentioning
confidence: 99%